My big fat Greek wedding 3 [videorecording (DVD)] - Economou, Stephanie; Vardalos, Nia, 1962-; Vardalos, Nia, 1962-; Corbett, John, 1961-; Mandylor, Louis; Kampouris, Elena, 1997-; Carides, Gia, 1964-; Fatone, Joey, 1977-; Kazan, Lainie; Martin, Andrea, 1947-; Peterson, Barry (Universal, 2023)
Join the Portokalos family as they travel to a family reunion in Greece for a heartwarming and hilarious trip full of love, twists, and turns. Opa!